Significance of weed management in relation to weed dynamics, growth characters and productivity of sorghum [Sorghum bicolor (L.) Moench] cultivars - Jat, A. L.; Massey, J. X.; Yadav, S. L.; Jat, S. L. (Annals of Agricultural Research, 2014)
A field experiment was conducted at Udaipur to study the effect of weed management practices on growth and productivity of sorghum [(Sorghum bicolor L.) Moench] cultivars during kharif 2010. Results showed that other then weed free check, intercropping with cowpea + 1 HW recorded higher dry matter accumulation, plant height, grain and stover yield of sorghum compared to rest of treatments. Intercropping with cowpea + 1 HW recorded lesser density of all type of weed flora, it was found significantly superior to other treatments in arresting total weeds population and recorded 51.15, 51.08 and 51.11 and 41.80, 42.66 and 42.34 per cent reduction in monocot, dicot and total weeds compared to weedy check at 30 and 60 DAS, respectively. In weed dry matter accumulation this treatment followed same trend and above as reduced biomass of all types of weeds at 30 as well as 60 DAS